Thermal evolution and sintering of chondritic planetesimals: III. Modelling the heat conductivity of porous chondrite material - Henke, Stephan-Markus; Gail, Hans-Peter; Trieloff, Mario (Astronomy and astrophysics, 2016)
Context. The construction of models for the internal constitution and temporal evolution of large planetesimals, which are the parent bodies of chondrites, requires as accurate as possible information on the heat conductivity of the complex mixture of minerals and iron metal found in chondrites. The few empirical data points on the heat conductivity of chondritic material are severely disturbed by impact-induced microcracks modifying the thermal conductivity. Aims. We attempt to evaluate the heat conductivity of chondritic material with theoretical methods. Methods. We derived the average heat conductivity of a multi-component mineral mixture and granular medium from the heat conductivities of its mixture components. We numerically generated random mixtures of solids with chondritic composition and packings of spheres. We solved the heat conduction equation in high spatial resolution for a test cube filled with such matter. We derived the heat conductivity of the mixture from the calculated heat flux through the cube. Results. For H and L chondrites, our results are in accord with empirical thermal conductivity at zero porosity. However, the porosity dependence of heat conductivity of granular material built from chondrules and matrix is at odds with measurements for chondrites, while our calculations are consistent with data for compacted sandstone. The discrepancy is traced back to subsequent shock modification of the currently available meteoritic material resulting from impacts on the parent body over the last 4.5 Ga. This causes a structure of void space made of fractures/cracks, which lowers the thermal conductivity of the medium and acts as a barrier to heat transfer. This structure is different from the structure that probably exists in the pristine material where voids are represented by pores rather than fractures. The results obtained for the heat conductivity of the pristine material are used for calculating models for the evolution of the H chondrite parent body, which are fitted to the cooling data of a number of H chondrites. The fit to the data is good; likewise the fit is good with models assuming different porosity. This is an indication that more diagnostic meteorite data are needed to distinguish between porosity models.
Gesehen am 27.08.2019